Očekávání jednoty v soudním rozhodování? K § 13 občanského zákoníku - Tomáš Holčapek; Petr Šustek (Acta Universitatis Carolinae. Iuridica, 2022)
The article discusses the meaning and effect of section 13 of the Civil Code, which may arguably concern unity in judicial (and other) decisions and the need of explanation for a divergence from “precedent”. It contends that this provision does not per se create any obligation to follow previous decisions, but merely to explain why the court in a later case came to a different conclusion. If a “precedent” is neither a judgment (“nález”) of the Constitutional Court nor a specially published decision of another high-level court, it is up to the parties in the proceedings to draw the court’s attention to it. Otherwise they cannot legitimately expect the court to expressly discuss such prior decision.